Memory, Heritage, Consumption and Oblivion - Pérgolis-Valsecchi, Juan Carlos (Corporación Universitaria del Caribe, CECAR., 2020)
The Plaza-circus-theater La Serrezuela, in Cartagena, a place for collective enjoyment, was replaced by a shopping center, with a simulation of the old Plaza. The change from the communal ritual of the spectacle to the individualistic entertainment of consumption destroyed passion in all activities. Several buildings in Medellín and Bogotá were transformed and demolished to give way to activities based on the individualism of leisure as a support for consumption. Heritage buildings with a great presence in urban memory, representatives of the spirit of time in each city, show that there are moments in history in which society chooses oblivion.